Polysaccharide impregnation: a pretreatment method for improving scallop quality and flavor - Mengwen Sun; Huimin Lin; Chen Zeng; Shanggui Deng; Alessandra Guidi (Food Science and Human Wellness)
The quality and flavor of scallops changes during the fresh dry rehydration process. In order to control the changes after rehydration, a scallop pretreatment method was adopted. The pretreatment method involved impregnating fresh scallops with 0.2 g/100 mL konjac glucomannan (KGM), carrageenan (CA), and sodium alginate (SA) before the drying and rehydration process. After rehydration, the KGM treated samples had better water retention and the highest betaine content. The CA treated samples had a deepened yellow color and the highest content of flavoring amino acids (FAA) and inosine monophosphate (IMP). What’s more, a total of 77 volatile compounds were detected, with a maximum of 15 esters. The highest proportion in the four groups was eugenol, followed by n-hexadecanoic acid, methyl hexadecanoate etc. The SA group had no significant contribution in terms of quality and taste. The samples pretreated with KGM had the best quality, and those pretreated by CA had the best flavor.